2015
DOI: 10.1176/appi.ajp.2014.14121576
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Treatment of a Health Care Worker After Infection With Ebola Virus in Lagos, Nigeria

Abstract: A young single male health worker was admitted to the isolation ward of the infectious disease hospital in Lagos with Ebola virus disease, which he had contracted in the course of rendering services to the index case in Nigeria. Three weeks after the admission, he appeared confused and was sleeping poorly, talking tangentially, and exhibiting unruly, disruptive behavior toward those caring for him. His behavioral symptoms were worse during relatives' visits. The clinical management team considered a diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 7 publications
1
17
0
Order By: Relevance
“…The outbreak itself and the control measures may lead to widespread fear and panic, especially stigmatization and social exclusion of confirmed patients, survivors and relations, which may escalate into further negative psychological reactions including adjustment disorder and depression. [3][4][5] Sudden outbreaks of public health events always pose huge challenges to the mental health service system. Examples include the HIV/AIDS epidemic that captivated world attention in the 1980s and 1990s, the severe acute respiratory syndrome (SARS) in 2002 and 2003, the H1N1 influenza pandemic of 2009, the Ebola virus outbreak in 2013, and the Zika virus outbreak in 2016.…”
mentioning
confidence: 99%
“…The outbreak itself and the control measures may lead to widespread fear and panic, especially stigmatization and social exclusion of confirmed patients, survivors and relations, which may escalate into further negative psychological reactions including adjustment disorder and depression. [3][4][5] Sudden outbreaks of public health events always pose huge challenges to the mental health service system. Examples include the HIV/AIDS epidemic that captivated world attention in the 1980s and 1990s, the severe acute respiratory syndrome (SARS) in 2002 and 2003, the H1N1 influenza pandemic of 2009, the Ebola virus outbreak in 2013, and the Zika virus outbreak in 2016.…”
mentioning
confidence: 99%
“…Mohammed et al recently reported an interesting case study of a post-ebola mental disorder (8). The indexed case presents with confusion and disruptive behavior (8). Psychotherapy and anxiolytic drugs were used in this case (8).…”
Section: Dear Editormentioning
confidence: 89%
“…The indexed case presents with confusion and disruptive behavior (8). Psychotherapy and anxiolytic drugs were used in this case (8). Mohammed et al mentioned that brain sequela is the cause of the mental illness (8).…”
Section: Dear Editormentioning
confidence: 94%
See 2 more Smart Citations